A Pala-Period Buddha Image with a Burmese Inscription from Galle - Frasch, Tilman (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
A Buddha image of the Pala Period was most probably transferred by a pilgrim to Burma in the 12th–13th century. The statue was engraved with a Burmese inscription in the 19th century and handed over as a donation to Sinhalese monks. They carried the statue on their journey back to Sri Lanka and today the image is kept in the Srī Paramananda Rājamahāvihāra at Galle. The article will be available as a PDF in the near future.